PENINGKATAN KESEHATAN MENTAL ANAK PRA SEKOLAH MELALUI EDUKASI TEKNOLOGI DIGITAL SEHAT : PENINGKATAN KESEHATAN MENTAL ANAK PRA SEKOLAH MELALUI EDUKASI TEKNOLOGI DIGITAL SEHAT - Amelia Susanti; Diana Arianti (Universitas Alifah Padang, 2026)
The rapid advancement of digital technology has significantly influenced how preschool children learn, play, and interact socially. While digital technology offers educational benefits and supports cognitive development, excessive and unsupervised use may negatively affect children's mental health, including emotional regulation difficulties, reduced social interaction, sleep disturbances, and behavioral problems. This community service program aimed to improve the knowledge and awareness of parents and teachers regarding healthy digital technology use to support preschool children's mental health. The activity was conducted in December 2025 at PAUD Tapian Bunda and involved 30 participants consisting of parents and teachers. The intervention included health education sessions, interactive discussions, demonstrations of age-appropriate digital technology use, and participant evaluations. The results indicated an improvement in participants’ understanding of screen-time limitations, parental supervision, age-appropriate content selection, and the importance of balancing digital activities with direct play and social interaction. Healthy digital technology education proved to be an effective promotive strategy for improving family digital literacy and preventing mental health problems among preschool children. Similar programs should be continuously implemented through collaboration among families, schools, and healthcare professionals.